ISLAMIC EDUCATION AS A SOLUTION TO THE INFLUENCE OF SOCIAL MEDIA ON ADOLESCENT BEHAVIOR - Hani Nursafwa; Alwan Abdurrafi (Proceeding International Seminar of Islamic Studies, 2022)
Social Media is currently the most known, used, and loved by teenagers, especially students.  The most frequently used social media today are Facebook, Instagram, Twitter, etc.  Easy network access nowadays makes students or teenagers use social media freely without thinking about the positive and negative impacts of social media.  As the nation's next generation, teenagers are categorized as the superior generation who can influence social life in terms of religion and social culture.  Meanwhile, with the rapid development of the digital era and very attached to the daily activities of adolescents based on the use of qualitative research methods from the results of investigations into adolescents, the researchers concluded that social networking has become something that can be said as a necessity for adolescents, Islamic religious education as a  one solution that provides a good understanding in terms of Ikhsan.  This paper aims to apply knowledge to the influence of Islamic Religious Education in social media.  The basis used to describe Islamic Religious Education as a Solution to the Effect of Social Media on Adolescent Behavior is to emphasize the Ikhsan attitude in the teenager, so that the reference used is the Al-Qur'an and Sunnah as well as the opinions of scholars who focus on Islamic education in this era.  the development of social media for adolescents, so that concluded if Islamic religious education that emphasizes Ikhsan in adolescents has the opportunity to influence adolescent behavior. Keywords: Islamic Education, Social Media Influence, Adolescent Behavior